1999
DOI: 10.1080/02688699943051
|View full text |Cite
|
Sign up to set email alerts
|

Spinal intradural tumours: Part II-intramedullary

Abstract: The results of surgical management in 54 patients with intramedullary spinal cord tumours are presented. Cervical tumours were most frequent (25/54) followed by thoracic (16/54) and then lumbar (14/54). Ependymomas and astrocytomas were the most common tumour types. Total tumour removal was possible in just over half of the cases. Surgical complications included: two deaths, six patients with CSF leaks and one with wound infection. Postoperatively three patients had worsening of their motor deficit (unable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 0 publications
4
53
0
2
Order By: Relevance
“…The meningioma recurrence was 5.5% in our study with a mean time to recurrence of 3 years and 1 month, which is comparable to other published studies [25]. Unsurprisingly, the majority of complications were due to dural CSF leak and meningitis, the incidence of which ranges from 5-13% and 1-10%, respectively [5,8,9,21,23]. Watertight dural closure is not always possible, especially with extramedullary meningiomas when the dura may be resected as part of the attempt to achieve complete excision.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The meningioma recurrence was 5.5% in our study with a mean time to recurrence of 3 years and 1 month, which is comparable to other published studies [25]. Unsurprisingly, the majority of complications were due to dural CSF leak and meningitis, the incidence of which ranges from 5-13% and 1-10%, respectively [5,8,9,21,23]. Watertight dural closure is not always possible, especially with extramedullary meningiomas when the dura may be resected as part of the attempt to achieve complete excision.…”
Section: Discussionsupporting
confidence: 85%
“…Some authors advise an aggressive surgical approach [8,9,17,20] but we adopt a different stance with the minimum bone removal to maintain spinal column stability and avoid the need for instrumentation, which makes post-operative MRI interpretation difficult. Only three patients deteriorated post-operatively, two remained ambulant, and one patient, who initially improved, developed MRSA meningitis leading to paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,22,26,32,33,36,44,46 The overall rate of tumor progression in our series was 47%, with a mean onset of 3 years postoperatively (mean [± SEM] 3.3 ± 1 years, range 0.1-20 years). Radiotherapy was used following disease progression or recurrence in 51% of the 55 patients, while chemotherapy was used in 29% of the patients.…”
Section: Role Of Adjunct Therapymentioning
confidence: 73%
“…In 1999 Kane et al 13 reported that the gait status was aggravated and unchanged in 6 (12%) and 45 (82%) of 54 patients with intramedullary tumors. In 1994 Cristante and Herrmann 5 reported that the outcome was aggravated, unchanged, and improved in 31, 55, and 17% of 69 intramedullary tumor cases, respectively.…”
Section: Discussionmentioning
confidence: 99%